The basque history of the world eaudiobook - Kurlansky, Mark (Recorded Books Inc., 2000)
Award-winning author Mark Kurlansky has drawn enthusiastic praise for his books, which are sharply-focused studies as well as glorious celebrations of their subjects. In The Basque History of the World, he turns his eye toward Europe's oldest surviving culture-a culture as mysterious as it is fascinating. Settled in the western Pyrenees Mountains of France and Spain, the Basque nation is not drawn on maps and the origin of their forbidden language has never been discovered. Yet, Basques appear to predate all other cultures in Europe, with many significant global contributions to their credit. Most notably, one of their own took command after Magellan's death and was the first person to circumnavigate the globe. This informative book is full of lively anecdotes that illuminate an otherwise obscure culture. Narrator George Guidall rises to the challenge of the text, which includes many Basque terms, and interprets beautifully.